2020
DOI: 10.3389/fmicb.2020.551444
|View full text |Cite
|
Sign up to set email alerts
|

Rhizosphere Bacterial Community Response to Continuous Cropping of Tibetan Barley

Abstract: Long-term continuous cropping influences the nutrient of soil and microbiome of the rhizosphere, resulting in the yield decrease of crops. Tibetan barley is a dominant cereal crop cultivated at high altitudes in Tibet. Its growth and yield are negatively affected by continuous cropping; however, the response of the rhizosphere microbial community to continuous cropping remains poorly understood. To address this question, we investigated the bacterial community structure and conducted predictive functional prof… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
15
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(18 citation statements)
references
References 71 publications
3
15
0
Order By: Relevance
“… Zhao et al (2020) showed that bacterial richness (ACE) significantly decreased after 5–10 years of continuous cropping and recovered after 30 years, while bacterial diversity (Shannon) significantly increased after continuous cropping (5, 10, and 30 years). In the present study, bacterial diversity (Shannon) did not differ during short continuous cropping years, but bacterial richness (Chao1 and ACE) and PD significantly declined after short-term continuous cropping of Tibetan barley, which is consistent with the findings of Yao et al (2020) , but surprisingly recovered after long-term continuous cropping ( Table 1 ). This phenomenon may be due to the fact that all environmental filters require specific adaptation strategies for survival; stronger selection acting on bacteria often leads to a new cohort of microbiota that adapt to the environment ( Fierer, Bradford & Jackson, 2007 ; Meola, Lazzaro & Zeyer, 2014 ).…”
Section: Discussionsupporting
confidence: 89%
See 3 more Smart Citations
“… Zhao et al (2020) showed that bacterial richness (ACE) significantly decreased after 5–10 years of continuous cropping and recovered after 30 years, while bacterial diversity (Shannon) significantly increased after continuous cropping (5, 10, and 30 years). In the present study, bacterial diversity (Shannon) did not differ during short continuous cropping years, but bacterial richness (Chao1 and ACE) and PD significantly declined after short-term continuous cropping of Tibetan barley, which is consistent with the findings of Yao et al (2020) , but surprisingly recovered after long-term continuous cropping ( Table 1 ). This phenomenon may be due to the fact that all environmental filters require specific adaptation strategies for survival; stronger selection acting on bacteria often leads to a new cohort of microbiota that adapt to the environment ( Fierer, Bradford & Jackson, 2007 ; Meola, Lazzaro & Zeyer, 2014 ).…”
Section: Discussionsupporting
confidence: 89%
“…A relevant study pointed out that the continuous cropping of Tibetan barley significantly increased the bacteria associated with chemo-heterotrophy, aromatic compound degradation, and nitrate reduction ( Yao et al, 2020 ). This study showed that the dominant shared genera, Sphingomonas , exerted significant negative effects on nitrification gene abundances ( amoA and nxrA ), leading to the imbalance of nitrification and denitrification.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…As growing cycles of replanting can be very short (e.g., less than 4 weeks for some leafy greens) in CEA systems, replant disease and negative legacy effects during certain planting generations can be significant due to nutrient consumption, rhizosphere bacterial community reshaping, and unfavorable rhizodeposition ( Yuan et al, 2018 ; Sun et al, 2019 ; Yao et al, 2020 ). There were clear legacy effects from moisture regimes prior to planting on soil, specifically in terms of physicochemical properties, plant growth and nutrition, and the formation of microbial responsiveness ( Cavagnaro, 2016 ).…”
Section: Introductionmentioning
confidence: 99%